PENGARUH FAKTOR SOSIO-DEMOGRAFIS TERHADAP PERSEPSI MASYARAKAT TENTANG DAMPAK PENGEMBANGAN PARIWISATA DI KABUPATEN PURWAKARTA: THE INFLUENCE OF SOCIO-DEMOGRAPHIC FACTORS ON COMMUNITY PERCEPTION OF TOURISM DEVELOPMENT IMPACTS IN PURWAKARTA REGENCY - Qurrota'ayun Fidelitasari; Ahmad Hudaiby Galih Kusumah; Mamat Ruhimat (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Bogor, 2024)
Tourism has emerged as a significant economic driver in many regions, yet its impacts on local communities remain a topic of debate. This study delves into the perceptions of residents in Purwakarta Regency, Indonesia, regarding the effects of tourism development. By employing a quantitative approach with a questionnaire distributed to 252 respondents, the research aims to uncover the underlying factor structure of these perceptions and investigate the influence of socio-demographic characteristics. The findings reveal that one key variable, “Working in the Tourism Industry”, has a significant bearing on how locals perceive tourism impacts. Despite concerns about potential negative consequences, the community generally supports the growth of the tourism sector. This research contributes to a deeper understanding of the complex interplay between socio-demographic factors and community perceptions. The insights gained can guide stakeholders in formulating effective and sustainable tourism development strategies that actively involve and benefit the local population.